2021
DOI: 10.1002/advs.202004554
|View full text |Cite
|
Sign up to set email alerts
|

Flexophotovoltaic Effect in Potassium Sodium Niobate/Poly(Vinylidene Fluoride‐Trifluoroethylene) Nanocomposite

Abstract: Flexoelectricity is an electromechanical coupling effect in which electric polarization is generated by a strain gradient. In this investigation, a potassium sodium niobite/poly(vinylidene fluoride-trifluoroethylene) (KNN/PVDF-TrFE)-based nanocomposite is fabricated, and the flexoelectric effect is used to enhance the photovoltaic current (I pv ) in the nanocomposite. It is found that both a pyroelectric current and photovoltaic current can be generated simultaneously in a light illumination process. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…According to the data in Figure c, there was no obvious rectification effect from the heterojunction (Schottky junctions) in the PZT-NW/PDMS-based nanocomposite, which was in accordance with the results of Guo et al. and Wang et al , …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…According to the data in Figure c, there was no obvious rectification effect from the heterojunction (Schottky junctions) in the PZT-NW/PDMS-based nanocomposite, which was in accordance with the results of Guo et al. and Wang et al , …”
Section: Resultssupporting
confidence: 82%
“…25 Recently, Wang et al in our group discovered flexoelectricity-enhanced photovoltaic (FPV) effect in a potassium sodium niobate (KNN)/PVDF-TrFE nanocomposite and found that the I pv of the composite film was enhanced by 13.9% due to the FPV effect. 26 We demonstrated that nanoparticle doping contributes to a high flexoelectric coefficient and a growing FPV effect in a nanocomposite. However, the basic principle of the high flexoelectric coefficient and flexophotovoltaic effect in the composite is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…[208][209][210][211] However, these composites are out of the scope of this review, and the progress in these composites has been summarized in the recent reviews. [208][209][210] One has to note that ferroelectric composite materials have shown great potentiality for many other new applications such as ferroelectric memory devices, [212,213] flexo-photovoltages, [213] and advanced nano-/micro-electromechanical systems based on flexoelectric composites. [214,215] In addition, the ferroelectric nanocomposite may be a good platform for exploring nontrivial topology in ferroelectrics.…”
Section: Other Compositesmentioning
confidence: 99%
“…[19,25] This makes the flexoelectric modulation of FEPV behavior a local effect with limited scalability. Macroscopic flexoelectric effect can be achieved by bending a flexible film, [22,26,27] but the generated strain gradients were typically small (<10 5 m −1 ) and hence the modulation of the FEPV effect by bending was not significant (e.g., the bendinginduced photo voltage change was within ≈0.1 V [22] ). Therefore, alternative approaches are needed to obtain large macroscopic flexoelectric effect and consequent significant and scalable modulation of the FEPV effect.…”
Section: Introductionmentioning
confidence: 99%